Conditional Knockout of Bmal1 in Corticotropin-Releasing Factor Neurons Does Not Alter Sleep–Wake Rhythm in Mice - Hung, Chi Jung; Yamanaka, Akihiro; Ono, Daisuke (Frontiers in Neuroscience, 2022)
Sleep and wakefulness are regulated by both the homeostatic mechanism and circadian clock. In mammals, the central circadian clock, the suprachiasmatic nucleus, in the hypothalamus plays a crucial role in the timing of physiology and behavior. Recently, we found that circadian regulation of wakefulness was transmitted via corticotropin-releasing factor (CRF) neurons in the paraventricular nucleus of the hypothalamus to orexin neurons in the lateral hypothalamus. However, it is still unclear how the molecular clock in the CRF neurons contributes to the regulation of sleep and wakefulness. In the present study, we established CRF neuron-specific Bmal1 deficient mice, and measured locomotor activity or electroencephalography and electromyography. We found that these mice showed normal circadian locomotor activity rhythms in both light-dark cycle and constant darkness. Furthermore, they showed normal daily patterns of sleep and wakefulness. These results suggest that Bmal1 in CRF neurons has no effect on either circadian locomotor activity or sleep and wakefulness.